Higher prevalence of metabolic disorders in patients with bilateral primary aldosteronism than unilateral primary aldosteronism. (24th September 2020) - Zhang, Zhihua; Luo, Qin; Tuersun, Tilakezi; Wang, Guoliang; Wu, Ting; Zhang, Delian; Wang, Menghui; Zhou, Keming; Sun, Le; Yue, Na; Li, Nanfang
Abstract: Objective: Metabolic syndrome (MetS) is a frequent clinical condition in hypertension patients and is more frequently reported in primary aldosteronism (PA). This study is aimed at investigating the prevalence of MetS and its components in the two major types of patients with adrenal venous sampling (AVS)‐confirmed unilateral PA and bilateral PA. Design and patients: This was a retrospective cross‐section study. We analysed metabolic parameters from 169 PA patients subtyped by AVS, including 85 unilateral PA patients and 84 bilateral PA patients, and we also included 169 non‐PA patients matched for age and sex. Results: Patients with unilateral PA had higher concentrations of aldosterone and lower serum potassium than patients with bilateral PA. However, patients with bilateral PA had higher prevalence of MetS (79.8% vs 64.7%, P = .029), obesity (40.5% vs 24.7%, P = .029), dyslipidemia (72.6% vs 55.3%, P = .019) and hyperglycaemia (29.8% vs 16.5%, P = .040) than those with unilateral PA. Meanwhile, bilateral PA had higher BMI (27.55 ± 4.58 vs 25.57 ± 3.28 kg/m 2, P = .001), waist circumference (98.54 ± 11.44 vs 93.32 ± 10.64 cm, P = .003) and fasting plasma glucose (4.98 ± 1.16 vs 4.64 ± 0.93 mmol/L, P = .034). The logistic regression analysis also showed that bilateral PA was associated with the presence of MetS after adjustment for age, sex and duration of hypertension. Conclusions: Patients with bilateral PA have a higher prevalence of MetS than those with unilateral PA, despite unilateral PA patients exhibiting higher concentrations of aldosterone and lower serum potassium, suggesting that unilateral PA and bilateral PA may have differing mechanisms of MetS.